The Meaning and Implications of the Use of Chickens in the Aqiqah Tradition:A Living Hadith Study in Torosiaje Jaya Village - Langke, Delsi; Laiya, Fitria N.; Anwar, Ferlin (International Journal on Advanced Science, Education, and Religion, 2025)
The Islamic tradition of aqiqah is normatively prescribed by the slaughter of a goat as a form of gratitude for the birth of a child. However, the people of Torosiaje Jaya Village practice the qukkor tradition by slaughtering a chicken as an alternative form that has developed through generations. This study aims to uncover the meaning and implications of using chickens in the aqiqah tradition and examine the implementation of living hadith in this local cultural practice. Using qualitative methods with an anthropological and historical approach, as well as thematic hadith analysis (maudhu'i), this study found that the qukkor tradition reflects the adaptation of hadith values in the socio-economic context of the community. In addition to preserving local culture, this practice strengthens social solidarity and the community's religious identity. Differences in community understanding between the slaughter of chickens and goats reflect the dynamics of the meaning of hadith in everyday life, making this tradition a concrete representation of living hadith that develops in the local cultural realm.